Home Automation using ESP-32 Development Board with Alexa Voice Assistant and Manual Switch - SUBKI, MUHAMMAD NAZHIIM BIN SUBKI; BAKAR, LILYWATI BINTI BAKAR; ABDUL WAHAB, ZURINA BINTI ABDUL WAHAB (Progress in Engineering Application and Technology, 2023)
Malaysia is a Southeast Asian country with a population of over 32 million people and a rapidly growing economy. It is known for its diverse culture, natural beauty, and advanced infrastructure. In recent years, Malaysia has also become a leader in the adoption and development of home automation systems, which allow homeowners to control and monitor various appliances in their homes remotely, using a computer or a smartphone. These systems can include features such as energy management, security and surveillance, entertainment, and communication. In this project, we developed a home automation system that uses a NodeMCU microcontroller and Alexa voice recognition to control and monitor various appliances in a home. The system allows users to control the appliances using voice commands through Alexa, a virtual button from the Alexa application interface and also provides a manual switch which can turn on and off when Alexa is in offline mode. In addition, this Alexa Amazon application is cross-platform, which means it can be used on both Android and iOS as a monitoring platform in this project. The system developed in this project is using a combination of hardware and software components, including the NodeMCU as a microcontroller, relay, user interface and others. The system integrates with Alexa and uses voice commands as the primary means of communication between the user and the appliances.